Noetnana Livestock Farmer Group Capacity Building Strategy in Fatukoa Village By Bank Indonesia Representative Office NTT Province Towards Micro, Small and Medium Enterprises (MSMEs) Digital 4.0 - HADI, Abdul; DJAHA, Ajis Salim Adang; KELLEN, Pius Bumi (PT Keberlanjutan Strategis Indonesia, 2023)
This research is a descriptive research with a qualitative approach which was carried out in the Noetnana Livestock Farmer Group in Fatukoa Village, Maulafa District, Kupang Regency, which is a group of livestock farmers assisted by the Representative Office of Bank Indonesia, NTT Province. The informants in this study were determined using a purposive technique, totaling 32 people with primary and secondary data types collected through observation, interview and document search techniques. The results of the study found that the strategy for developing the capacity of the Noetnana Livestock Farmers Group in Fatukoa Village by the Representative Office of Bank Indonesia in the Province of NTT towards Digital 4.0 MSMEs, the authors used the opinion of Thompson (2003: 60) who developed the concept created by Parsons (1960), wherein: (a ) technical level, it was found that there was technical support in the form of policy, budget and program support provided by Bank Indonesia to the Noetnana Livestock Farmers Group to support MSMEs technically non-financially, such as mentoring & consulting assistance, infrastructure, motivation, and further technology at (b) level managerially it was found that there was an allocation of personnel for each unit and function in supporting the capacity building of the Noetnana Livestock Farmers Group while at (c) the institutional level it was found that there was an increase in the group's institutional capacity.